2019
DOI: 10.1111/ejh.13311
|View full text |Cite
|
Sign up to set email alerts
|

A previously unrecognized Ankyrin‐1 mutation associated with Hereditary Spherocytosis in an Italian family

Abstract: Hereditary spherocytosis is the most common inherited hemolytic anemia characterized by the presence of spherical-shaped erythrocytes on peripheral blood smear.The clinical manifestations of HS are highly variable, from severe forms to asymptomatic forms. HS is caused by defects in red blood cell membrane proteins, encoded by the ANK1, EPB42, SLC4A1, SPTA1 and SPTB genes. Mutation of the ANK 1 gene is the most common and inheritance is autosomal dominant in 75% of cases. In our case, heterozygous an ANK1 c.412… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Shen et al, 2019), ID3 (Eber et al, 1996), ID4 (Lazzareschi et al, 2019), ID7 (Wang et al, 2017), ID12 (Wang et al, 2017), and ID14 (Aggarwal et al, 2020) have been reported in the past. The ANK1 C.4276C > T (p.r1426 * ) variant was found in both patients 7 and 12.…”
Section: Mutational Spectrum Of Hs Patientsmentioning
confidence: 96%
“…Shen et al, 2019), ID3 (Eber et al, 1996), ID4 (Lazzareschi et al, 2019), ID7 (Wang et al, 2017), ID12 (Wang et al, 2017), and ID14 (Aggarwal et al, 2020) have been reported in the past. The ANK1 C.4276C > T (p.r1426 * ) variant was found in both patients 7 and 12.…”
Section: Mutational Spectrum Of Hs Patientsmentioning
confidence: 96%
“…Moreover, instability of the cell membrane is observed in some blood disorders, such as hereditary spherocytosis, hereditary stomatocytosis, and hereditary elliptocytosis, where protein defects in the vertical and horizontal interactions were demonstrated [67,74]. All these pathologies have in common the fact that they present alterations in some cytoskeleton component, and consequently alterations in the morphology and mechanical properties of erythrocytes were observed, for example, in hereditary spherocytosis, quantitative or qualitative defects were observed in ankyrin, protein 4.2, band 3 protein, α-spectrin, and β-spectrin, which are encoded by the ANK1, EPB42, SLC4A1, SPTA1, and SPTB genes, respectively [75]. On the other hand, in hereditary elliptocytosis, heterozygous mutations of genes that encode the α-spectrin (encoded by SPTA1), β-spectrin (encoded by SPTB), or protein 4.1 were reported [76].…”
Section: Mechanical Changes During Reticulocyte Maturationmentioning
confidence: 98%